THE USE OF FINANCIAL RATIO AND BUSINESS RISK ANALYSIS TO PREDICT FINANCIAL DISTRESS IN INDONESIA - Gabriela Puspita Rani Wibowo (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aims at obtaining empirical data on profitability ratio, liquidity ratio, solvability ratio, asset utilization efficiency ratio, and business risk (ERM disclosure) in predicting the financial distress of manufacturing companies in Indonesia. This research is also projected to seek for empirical evidence that Multiple Discriminant Analysis model is valid in predictor of the financial distress of manufacturing companies in Indonesia. 124 companies listed in Indonesia Stock Exchange (IDX) during period of 2014-2015 are purposively selected as the research samples. The data of 2016 are used as the model application. The results of the study indicate that the profitability, solvability, and business risk (ERM disclosure) variables can predict financial distress. On the other hand, liquidity and asset utilization efficiency can not predict financial distress. 84.7% of discriminant analysis is able to predict properly the financial distress condition in 2014-2015; meanwhile, 91.9% of the discriminant analysis can predict accurately the condition in 2016. Keywords: Financial Distress, profitability, liquidity, solvability, asset utilization efficiency, ERM disclosure, Multiple Discriminant Analysis